1992
DOI: 10.1007/bf02257622
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical markers in the cerebrospinal fluid of patients with Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis and normal controls

Abstract: Several neurotransmitter markers were investigated in the cerebrospinal fluid (CSF) from patients with Alzheimer's disease (AD) (n = 27), Parkinson's disease (PD) (n = 35) and ALS (n = 26) and from control subjects (n = 34) to compare the possible alterations in the biochemical profiles of these different neurodegenerative diseases. The main proportion of the patients represented an early phase of the illness at the time of the diagnosis. Correlations of the degree of dementia and the stage of the disease with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 71 publications
3
15
0
Order By: Relevance
“…Table 1 presents the 5-S-CyS-DA and HVA levels and the 5-S-CyS-DA/ HVA concentration ratios measured in the CSF of 20 PD patients maintained on Madopar (PD-LT patients), the same patients 5 days after this drug was discontinued (PD-LW patients), and for 16 controls. The mean level of HVA was significantly lower (p = 0.001) in the CSF of PD-LW patients (22.32 _+ 5.08ngmL-~; mean _+ SEM) than in that of controls (46.30 +_ 4.09ngmL I) in agreement with the results of previous studies (Hartikainen et al, 1992;Chia et al, 1993;Gonzalez-Quevedo et al, 1993). After Madopar administration (i.e., PD-LT patients), mean CSF levels of HVA increased to 43.53 _+ 6.20ngmL -1 (p < 0.05 compared to PD-LW patients) and reached approximately the same concentration measured in controls (46.30 _+ 4.09ngmL-1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Table 1 presents the 5-S-CyS-DA and HVA levels and the 5-S-CyS-DA/ HVA concentration ratios measured in the CSF of 20 PD patients maintained on Madopar (PD-LT patients), the same patients 5 days after this drug was discontinued (PD-LW patients), and for 16 controls. The mean level of HVA was significantly lower (p = 0.001) in the CSF of PD-LW patients (22.32 _+ 5.08ngmL-~; mean _+ SEM) than in that of controls (46.30 +_ 4.09ngmL I) in agreement with the results of previous studies (Hartikainen et al, 1992;Chia et al, 1993;Gonzalez-Quevedo et al, 1993). After Madopar administration (i.e., PD-LT patients), mean CSF levels of HVA increased to 43.53 _+ 6.20ngmL -1 (p < 0.05 compared to PD-LW patients) and reached approximately the same concentration measured in controls (46.30 _+ 4.09ngmL-1).…”
Section: Resultssupporting
confidence: 93%
“…As noted by previous investigators (Hartikainen et al, 1992;Chia et al, 1993;Gonzalez-Quevedo et al, 1993), the mean HVA levels in the CSF of PD-LW patients (22.32 +_ 5.08ngmL -1) was significantly (p = 0.001) lower than that measured in the CSF of controls (46.30 _+ 4.09ngmL-1). The fact that, on average, CSF levels of HVA are reduced by only ca.…”
Section: Discussionsupporting
confidence: 39%
“…A heterogenous degeneration of multiple neuronal networks may reflect a generalized brain disorder relating to senile dementia of Alzheimer type (SDAT) (Quinn et al, 1986;Jellinger, 1991;Griffiths et al, 1994). Neurochemical and immunohistochemical studies suggest al least three dementia syndromes in PD: the most common is a consequence of dopamine deficiency, another results from combined dopaminergic and cholinergic deficiencies (Kawakatsu et al, 1990;Jellinger, 1986;Konings et al, 1995) and a third represents combined PD and SDAT with an additional varying involvement of other neurotransmitters, like serotonin (Gottfries et al, 1983;Herregodts et al, 1989) and SDAT-typical neuromodulators such as somatostatin (Leake and Ferrier, 1993;Unsicker, 1993;Hartikainen et al, 1992).…”
Section: Introductionmentioning
confidence: 97%
“…As regards SLI in the CSF, no change was found between ALS patients and normal subjects [168]. Nieto-Gonzalez et al found a decreased density of parvalbumin-and SST-positive inhibitory interneurones and reduced vesicular GABA transporter immunoreactivity in the neuropil of the wobbler mouse, an animal model of ALS.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%